Synchronizing Decentralized Control Loops for Overall Performance Enhancement: A Youla Framework Applied to a Wafer Scanner. Issue 1 (July 2017) - Evers, Enzo; van de Wal, Marc; Oomen, Tom
Abstract: Manufacturing equipment often consists of multiple subsystems. For instance, in lithographic IC manufacturing, both a reticle stage and a wafer stage move synchronously. Traditionally, these subsystems are divided into manageable subproblems, at the expense of a suboptimal overall solution. The aim of this paper is to develop a framework for overall system performance improvement. The method pursued in this paper builds on traditional designs, and extends these through a bi-directional controller coupling. The aim here is to optimize a criterion that speciés overall system performance. To achieve this, a new parameterization that relates to the Youla parameterization is developed that connects the bi-directional controller parameter affinely to the overall control criterion, which enables a systematic design. The performance improvement is confirmed in a case study using measured data from an industrial wafer scanner.